Analisis Segmentasi dan Penargetan Pasar Sneakers Lokal di Jabodetabek - Farras, Muhammad Ammar; Muhammad Rafi; Farhan, Mohamad; Riorini, Sri Vandayuli (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
In recent years, public perception of local footwear products has shifted positively along with increasing awareness to support domestic products. Changes in consumer preferences, the development of e-commerce, and demands for quality and sustainability are important factors in forming an effective marketing strategy. This study aims to describe the segmentation and target market for local footwear, especially sneakers, and to design a marketing strategy based on the marketing mix approach (4P: Product, Price, Place, Promotion). This study uses a descriptive method with primary data collection through consumer interviews. The sampling technique used is purposive sampling, and data analysis is carried out using cluster analysis, both hierarchically and non-hierarchically. The results of the analysis show the formation of four market segments, with the fourth segment as the most potential target because it has the highest mean value for the product variable. The findings show that consumers prioritize comfort, prices that are comparable to quality, strategic store locations, and the influence of social media in the purchasing decision-making process. Recommended strategies include emphasizing ergonomic design, competitive pricing, optimizing offline and online distribution channels, and attractive digital content-based promotional campaigns.